Yummy Mummy — The ideal of not looking like a mother. Issue 3 (May 2020) - Prinds, Christina; Nikolajsen, Helene; Folmann, Birgitte
Abstract: Background: Pregnancy and childbirth are important life experiences that entail major changes, both physically, psychologically, socially and existentially for women. Motherhood transition and the accompanying bodily changes involve expectations of body image that are simultaneously naturally and socially produced and culturally informed by public, private and professional discourses about motherhood transition. Problem: Much focus is levelled at the antepartum body in maternity services whereas the postpartum body seems left alone, although bodily dissatisfaction is of concern for many mothers, whose expectations of bodily appearance postpartum are sharp and explicit. Aim: To explore Danish first-time mothers' experiences of their body postpartum, focusing on body image. Methods: Eleven first-time mothers participated in semi-structured interviews related to the postpartum body image. Data was analysed thematically. Findings: Four themes: (1) Reverting the body: on bouncing back and losing weight; (2) Picturing me: on standards of beauty and ideal bodies; (3) Redefining earlier self-images: on meta-reproachment of the body; (4) Idealisation of not looking like a mother: on societal pressure to think positively. Findings were discussed through the theoretical concepts by Scheper-Hughes and Lock: the body as both individual, social and political. Conclusion: Despite nuanced reflections over the body as subject and object, women identified beauty as a personal trait dependent on visual appearance. Bodily beauty was identified as something individual, yet standardised. Women felt strengthened through motherhood but looking like a mother was not considered worth pursuing. To allow for women's contradictory perspectives, caregivers are advised to communicate reflexively about the postpartum body.